How does entrepreneurs' psychological ownership affect their grief after failure?. (2017) - Hsu, Dan K.; Burmeister-Lamp, Katrin; Hong, Michelle
What determines the level of grief that entrepreneurs feel after failure? Drawing on regulatory focus theory and the psychological ownership (PO) literature, this paper examines the effect of different components of PO the failed entrepreneurs have had toward the prior venture on their grief levels. It is argued that PO has two components: promotive PO, which is driven by the individual's achievement needs, and preventative PO, which is driven by the safety needs. Surveying 150 individuals with business failure experience, this study found that individuals with stronger promotive PO toward the prior venture felt less grief while individuals with greater preventative PO incurred stronger grief feelings.